Self-reported concussion prevalence, post-injury help-seeking behaviour, and associated risk factors among volleyball players - Gamze Nedzhipoglu; Amanda Johnson; Nick Dobbin (PLoS ONE, 2025)
Background Volleyball is an under-researched sport, particularly in relation to risk factors for head impacts and sports-related concussion (SRC). This study aimed to estimate the self-reported lifetime prevalence of SRC, post-injury help-seeking behaviour, and associations between SRC and age, sex at birth, playing experience, playing league, and playing position. Methods A cross-sectional study was conducted using an online questionnaire to examine lifetime prevlaance and associations between SRC and personal and sport-related factors. The questionnaire collected demographic information, SRC history, and help-seeking behaviour. Descriptive statistics were used to estimate SRC prevalence and help-seeking behaviours among players with a history of SRC. A mixed-effect binary logistic model was conducted at a univariable and multivariable level to assess associations between SRC with playing experience, league, position, age, and gender. Results A total of 74 volleyball players, 44 females and 30 males, completed the questionnaire. The estimated self-reported lifetime prevalence of SRC was 35% (males 33%, females 36%). Medical support was limited both during and following a SRC. Only 39% of players reporting a SRC were diagnosed, with just 23–27% seeking medical help. Older and more experienced athletes had higher odds of reporting SRC. Those aged 28 years and above showed greater odds (OR=4.58–8.91) of reporting a SRC compared to those aged 16–21, and those with more than 13 years of experience showed greater odds (OR=4.04–9.51) than those with 1–3 years’ experience. Professional players showed reduced odds (OR=0.05) compared to high school and university players in the multivariable model. Conclusions SRC occur in volleyball with a lifetime prevalence of 35%, yet many incidents go undiagnosed and unmanaged. Older, more experienced players had greater odds of reporting a SRC, while professional-level athletes showed reduced odds when all factors are considered. Increased awareness and appropriate guidance are needed across all levels in volleyball.